Does Impact of Using an Online Learning on Salesmanship Course in The Era Covid 19 Pandemic? - Harti; Raya Sulistyowati; Tri Sudarwanto; Septyan Budi Cahya; Veni Rafida; Tareq Furas (IJORER : International Journal of Recent Educational Research, 2021)
This research aims to explore the application of learning salesmanship courses during the COVID-19 pandemic, where there are social policies and physical distance conducted by online lectures, while salesmanship courses will be effective if done with many direct practices. Approved implementation of planning, implementation, and evaluation of the implementation of online learning with the support of learning applications such as learning modules and videos. This research was conducted using descriptive qualitative, discussion, and collect data about responses and submissions of learning applications consisting of modules and video sales used during the online learning process. The technique of collecting data is done by collecting, observing, and questioning. Data were analyzed qualitatively using NVIVO software. The results showed that learning tools in the form of salesmanship modules and videos received very high responses, and were effective in fostering student interest in learning, the results of data analysis showed that with modules and videos made learning salesmanship easier, especially on the topic of effective selling techniques online at a pandemic period, very relevant to current needs.